2000
DOI: 10.1002/1097-0215(20000901)87:5<734::aid-ijc17>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of alcohol dehydrogenase 3 and cytochrome P‐4502E1 genotypes in susceptibility to cancers of the upper aerodigestive tract

Abstract: Alcohol is a recognized risk factor for upper aerodigestive tract (UAT) cancers, but the mechanism by which alcohol causes cancer remains obscure. Ethanol is oxidized to acetaldehyde (the suspected carcinogenic agent in alcohol) by alcohol dehydrogenases (ADHs) and cytochrome P-4502E1 (CYP2E1), both of which exhibit great inter-individual variability in activity. The hypothesis that these polymorphisms influence susceptibility to alcohol-related cancers remains poorly documented. We investigated whether ADH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…37 Therefore, perhaps we should not be surprised to find multiple genetic differences between the Greek and other European populations, as well as even greater differences with populations such as those in Puerto Rico where Hispanic-Native American-African admixture has occurred. 38 As we noted in the introduction, a recent study conducted in France found no significant evidence of an effect of the ADH 3 SNP on OC risk, 24 consistent with a previous analysis of the same study subjects. 40 In contrast to the findings obtained in Puerto Rico, the effect of this SNP on OC risk did not seem to be influenced by amounts of alcohol consumed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…37 Therefore, perhaps we should not be surprised to find multiple genetic differences between the Greek and other European populations, as well as even greater differences with populations such as those in Puerto Rico where Hispanic-Native American-African admixture has occurred. 38 As we noted in the introduction, a recent study conducted in France found no significant evidence of an effect of the ADH 3 SNP on OC risk, 24 consistent with a previous analysis of the same study subjects. 40 In contrast to the findings obtained in Puerto Rico, the effect of this SNP on OC risk did not seem to be influenced by amounts of alcohol consumed.…”
Section: Discussionsupporting
confidence: 83%
“…Evidence of this SNPs interaction with alcohol consumption in OC risk was reported in a case control study conducted in Puerto Rico. 6 By contrast, in a study recently reported using a French population, 24 no association was found with the ADH 3 SNP but an association was reported for CYP2E1.…”
mentioning
confidence: 80%
“…16,17,[32][33][34] We failed to observe an association between ADH 3 gene polymorphisms and the development of lung cancer, most likely because of the limited statistical power from the low frequency of the variant allele in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated the common genotype or alleles to confer greater risk of oral [15] , pharyngeal [15] , esophageal [16,17] liver [18] and lung [19,20] cancers. On the other hand, increased risk of oral [21] , nasopharyngeal [22] , liver [23] and colorectal [24,25] cancers was observed with the rare genotype or allele carriers in other studies.…”
Section: Introductionmentioning
confidence: 99%